Sri Indriyani Nurhasanah - Nurhasanah, Sri Indriyani; Abduljabar, Bambang; Carsiwan, Carsiwan (Universitas Hamzanwadi, 2025)
This study aims to compare the teaching and learning process of PJOK subjects that implement the 2013 Curriculum and the Merdeka Curriculum. The study used a qualitative descriptive method with data collection techniques through questionnaires, interviews, and documentation. The population in the study was 82 students. Sampling using purposive sampling technique, the number was 64 students. The results showed that the 2013 Curriculum provides a more systematic and directed learning structure, which has a positive impact on students' active involvement and motivation. On the other hand, Merdeka Curriculum provides flexibility for teachers and students to explore learning according to local interests and contexts, but its implementation still faces challenges, such as teacher and student readiness, and understanding of formative assessment. The 2013 curriculum obtained a higher % “strongly agree”. Students' active engagement was generally higher in Curriculum 2013, with 86% of students expressing “agree” or “strongly agree” to various statements regarding their engagement in learning. Meanwhile, in the Merdeka Curriculum, the percentage decreased to 75%. The conclusion shows that Curriculum 2013 is more effective in increasing PJOK students' engagement and motivation due to structured and directed learning. Meanwhile, the Merdeka Curriculum offers greater flexibility and opportunities for exploration, but its implementation still faces challenges.